Autologous Intestinal Reconstruction Surgery in Short Bowel Syndrome: Which, When, and Why - Boroni, Giovanni; Parolini, Filippo; Stern, Maria Vittoria; Moglia, Cristina; Alberti, Daniele (Frontiers in Nutrition, 2022)
Short bowel syndrome, secondary to any natural loss or after any extensive bowel resection for congenital malformations or acquired disease, is the most common cause of intestinal failure in children. The extensive introduction of parenteral nutrition (PN) has dramatically changed the outcome of these patients, allowing a long-term survival. The main goal in children with short bowel syndrome remains to increase enteral tolerance and to wean from parenteral nutrition support. Post resection intestinal adaptation allows achievement of enteral autonomy in a subset of these patients, but the inability to progress in enteral tolerance exposes the others to long-term complications of PN. Autologous intestinal reconstruction surgery (AIRS) can facilitate the fulfilment of enteral autonomy, maximizing the absorptive potential of the remaining gut. All the different intestinal reconstruction techniques, from simple procedures like tapering, reversed segments and colon interposition to more complex lengthening procedures (LILT: Longitudinal Intestinal Lengthening and Tailoring, STEP: Serial Transverse EnteroPlasty; SILT: Spiral Intestinal Lengthening and Tailoring), and techniques designed for peculiar problems like controlled intestinal tissue expansion or duodenal lengthening, are presented. AIRS indications, clinical applications and results reported in the literature are reviewed.